Dementia elderly tracker using Sigfox - Neo, Yizhe (Nanyang Technological University, 2023)
Singapore has been grappling with the issue of an aging population for a number of years. As a result, some families have resorted to purchasing off-the-shelf location trackers designed for dementia patients. These trackers typically use Global System for Mobile communication (GSM) technology and require a SIM card. The aim of this project is to create a proof-of-concept dementia elderly tracker using Sigfox technology that operates without the need for a SIM card. This approach would lead to significant cost savings and greater flexibility in terms of operating locations. Leveraging IoT modules and sensors, the tracker will transmit data via Sigfox technology, which will then be displayed on Telegram for caregivers to keep track of the elderly's location and well-being. To prevent the wearer from removing the tracker and misplacing it, a wearable bracelet has been designed that can only be removed at an angle which is not known to the elderly.